Experimental study of Triglii semen(巴豆) on the blood in Rats - Dae-Hyun Kim; Kyeong-Sun Soh; Chan-Gil Jeong; Kwang-Ho Kim (Korean Pharmacopuncture Institute, 2005)
In order to Experimental study effects of 「Triglii Semen」on the blood in Rats , we have made rats by administering Animal control chamber for two weeks, then have administered. The results were summerized as follows: 1. The total cholesterol, triglyceride and Hct, Hb by generally rats oral ingestion by Triglii semen of the sample group were decreased as compared with those of the control group. 2. GOT, GPT by generally rats oral ingestion were increased as compared those of control group. According to the above results, Triglii Semen showed inhibition on decrease of serum total cholesterol and Hb, Hct, WBC, RBC contents as well as inhibition on increase of GOT, GPT.